Analysis The Mediating Role Of Future Work Self Salience On The Influence Of Proactive Personality To Career Adaptability Of Student Organizations Administrators In Preparing Themselves Entering The World Of Work - Faren Zhafran; Ariyani Erlin, Nia (Human Resource Management Studies, 2025)
This study aims to examine the mediating role of future work self-salience on the influence of proactive personality on the career adaptability of student organization administrators in preparing themselves to enter the workforce. The background of this study is that many students still believe that organizations are a waste of time, energy, and thought. In addition, many students consider participating in campus organizations to be unimportant and believe that it will have no impact when they enter the workforce. The sample size used was 120 students, selected using cluster random sampling. Data collection was conducted using a questionnaire with a Likert scale. The analysis method used was SEM-PLS through SmartPLS 4.1.4 software. The results of data processing in this study show that: (1) proactive personality has a positive and significant effect on the career adaptability of students who participate in student organizations at the Faculty of Economics and Business, UNP (2) proactive personality has a positive and significant effect on the future work self-salience of students who participate in student organizations at the Faculty of Economics and Business, UNP (3) Future work self-salience has a positive and significant effect on the career adaptability of students who participate in student organizations at the Faculty of Economics and Business, UNP. (4) Future work self-salience mediates the effect of proactive personality on the career adaptability of students who participate in student organizations at the Faculty of Economics and Business, UNP.